A randomized study on the value of self‐directed versus traditional mentor‐led microsurgical training. Issue 1 (3rd January 2023) - Powell, Michael S.; Gardner, James Reed; Davis, Kyle P.; Dunlap, Quinn; King, Deanne; Vural, Emre; Moreno, Mauricio Alejandro; Sunde, Jumin
Abstract: Objective: Analyze efficacy of self‐directed resident microvascular training versus a mentor‐led course. Study Design: Randomized, single‐blinded cohort study. Setting: Academic tertiary care center. Methods: Sixteen resident and fellow participants were randomized into two groups stratified by training year. Group A completed a self‐directed microvascular course with instructional videos and self‐directed lab sessions. Group B completed a traditional mentor‐led microvascular course. Both groups spent equal time in the lab. Video recorded pre and post‐course microsurgical skill assessments were performed to assess the efficacy of the training. Two microsurgeons, blinded to participant identity, evaluated the recordings and inspected each microvascular anastomosis (MVA). Videos were scored using an objective‐structured assessment of technical skills (OSATS), a global rating scale (GRS), and quality of anastomosis scoring (QoA). Results: The pre‐course assessment identified that the groups were well matched with only "Economy of Motion" on the GRS favoring the mentor led group ( p  = .02). This difference remained significant on the post assessment ( p  = .02) Both groups significantly improved in OSATS and GRS scoring ( p  < .05). There was no significant difference in OSATS improvement between the two groups ( p  = .36) or improvement in MVA quality between groups ( p  > .99). Time to completion of MVA significantly improved overall by a mean of 8 min and 9 s ( p  = .005) with no significant difference between post training times to complete ( p  = .63). Conclusion: Different microsurgical training models have previously been validated as effective methods for improved MVA performance. Our findings indicate that a self‐directed microsurgical training model is an effective alternative to a traditional mentor driven models. Level of Evidence: Level 2. Abstract : We designed a randomized, single‐blinded cohort study to analyze the efficacy of self‐directed resident microvascular training compared to a mentor‐led course. Our results suggest that a self‐directed microsurgical training model is an effective alternative to more traditional models.